Dynamic modelling and intelligent control of an unmanned surface vehicle - Chew, Bung Yuh (2018)
Unmanned ground vehicles (USV) are vehicles that operate on the surface of the water or on the sea without crew control. USVs are valuable in oceanography because they are more capable than moored or floating weather buoys but are much less expensive than comparable weather and research ships and more flexible than the merchant's contribution. Wave gliders, especially those used for main propulsion, as well as powering their electronic devices with solar cells, have lasting months of academic and naval durability. A valid USV is very popular in hydrography. Using small USVs alongside traditional survey vessels as "enhanced power" can double survey coverage and reduce on-site time. This method was done for a survey conducted in the Bering Sea, Alaska; ASV's global "C-Worker 5" autonomous surface vehicle (ASV) collected 2,275 nautical miles of survey data, accounting for 44% of the total number of projects. This is the first time the industry has surveyed, saving 25 days at sea.